Das linearbandkeramische Gräberfeld von Kleinhadersdorf - Neugebauer-Maresch, Christine (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The publication gives a complete documentation of the old rescue excavations by Josef Bayer and Viktor Lebzelter in 1931 as well as of the systematic investigations of the Neolithic cemetery under the direction of Johannes-Wolfgang Neugebauer and Christine Neugebauer-Maresch between 1987-1991. The burial customs of this early farming population are analyzed together with the grave goods, which comprise an exceptionally large number of grinding stones, as well as ceramics, bone tools, shell ornaments, chert and traces of red ochre. The results of analyses of anthropological remains pertaining to 57 inhumations − more than half of the bodies were oriented SE-NW and the majority buried in a crouched position on the left side − are complemented by 14C-dates and isotope-analyses.